2022
DOI: 10.3390/agriculture12081136
|View full text |Cite
|
Sign up to set email alerts
|

Rhizobium and Phosphate Solubilizing Bacteria Influence the Soil Nutrient Availability, Growth, Yield, and Quality of Soybean

Abstract: Crop production encounters challenges due to the dearth of nitrogen (N) and phosphorus (P), while excessive use of chemical fertilizers causes environmental hazards. Use of rhizobium and phosphate solubilizing bacteria (PSB) can be a sustainable strategy to overcome these problems. Hence, a pot experiment was conducted following a completely randomized design to explore the impact of nitrogen fixing bacteria and PSB on the growth, yield, and quality attributes of soybean alongside soil nutrient availability us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 74 publications
4
15
0
Order By: Relevance
“…Gaur et al [ 60 ] documented the solubilization of approximately 30–40 kg P 2 O 5 ha −1 due to the inoculation of P-solubilizing microbes. Besides, dual inoculation of beneficial microbes was proven to be more effective than single inoculation considering crop growth and yield because of the augmented effects [ 34 ]. Therefore, based on our experiment’s results, we can postulate that dual inoculation of soybean seeds with an N-fixing bacteria and P-solubilizing yeast leads to improved SDW and RDW.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Gaur et al [ 60 ] documented the solubilization of approximately 30–40 kg P 2 O 5 ha −1 due to the inoculation of P-solubilizing microbes. Besides, dual inoculation of beneficial microbes was proven to be more effective than single inoculation considering crop growth and yield because of the augmented effects [ 34 ]. Therefore, based on our experiment’s results, we can postulate that dual inoculation of soybean seeds with an N-fixing bacteria and P-solubilizing yeast leads to improved SDW and RDW.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found that SNP and PNP were significantly higher in soybeans under T5 and T6 when compared to the rest of the treatments ( Figure 4 ). Numerous studies have also found that SNP and PNP are significantly enhanced by dual inoculation of IAA-producing and P-solubilizing microbes [ 34 , 35 ]. This highlights the significance of using more than one microbial isolate as a biofertilizer since these isolates can enhance the effectiveness of each other in P solubilization and IAA production as shown in Figure 1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations